2017
DOI: 10.1016/j.optom.2016.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different types of astigmatism on visual acuity

Abstract: PurposeTo investigate the change in visual acuity (VA) produced by different types of astigmatism (on the basis of the refractive power and position of the principal meridians) on normal accommodating eyes.MethodsThe lens induced method was employed to simulate a set of 28 astigmatic blur conditions on different healthy emmetropic eyes. Additionally, 24 values of spherical defocus were also simulated on the same eyes for comparison. VA was measured in each case and the results, expressed in logMAR units, were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 34 publications
1
17
0
1
Order By: Relevance
“…We used the SEVA for the assessment of visual performance in astigmatic eyes, when the least circle of confusion is focused on the retina in the current study, in order to precisely investigate the effect of the amount of astigmatism on visual acuity. Remón et al also evaluated the SEVA when the least circle of confusion is focused on the retina in astigmatic eyes, but the subject age was much younger (25 to 32 years) 10 . To the best of our knowledge, this is the first study to assess the relationship between astigmatism and visual acuity in both phakic and pseudophakic elderly subjects, and to establish a prediction formula of distance visual acuity according to the amount of astigmatism in a large cohort of such subjects.…”
Section: Discussionmentioning
confidence: 99%
“…We used the SEVA for the assessment of visual performance in astigmatic eyes, when the least circle of confusion is focused on the retina in the current study, in order to precisely investigate the effect of the amount of astigmatism on visual acuity. Remón et al also evaluated the SEVA when the least circle of confusion is focused on the retina in astigmatic eyes, but the subject age was much younger (25 to 32 years) 10 . To the best of our knowledge, this is the first study to assess the relationship between astigmatism and visual acuity in both phakic and pseudophakic elderly subjects, and to establish a prediction formula of distance visual acuity according to the amount of astigmatism in a large cohort of such subjects.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was consistent with Cui Y’s [ 18 , 19 ] studies, which showed the same phenomenon after cataract surgery. However, the impact of the astigmatic axial on visual acuity was oblique> ATR > WTR astigmatism [ 20 ]. In our study, a higher percentage of oblique astigmatism but a much lower percentage of WTR astigmatism was found postoperatively in group B 2 compared with those in group A 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it is important to note that, like happens for the HCVA,4 the rate of change of the other visual parameters with the blur strength may depend on the type of residual astigmatism, and also on the amplitude of accommodation of the participants. This may be one of the reasons for the different slopes in the data corresponding to undercorrection by 0.75 DC in the above-mentioned Figure 2 (dotted line).…”
Section: Dear Editormentioning
confidence: 99%
“…However, it is well known that cylinder power and axis are not independent variables; in fact, astigmatism is a vector magnitude. Several studies2,4 use vector formalism to quantify the blur strength produced by astigmatism. Even in previous literature,1 the authors show the power vector components ( M, J 0 , J 45 ) in Table 1, for the different groups in which the sample is divided.…”
Section: Dear Editormentioning
confidence: 99%